تصورِ تحفظ ِناموسِ رسالت: قاضی عیاض کی " الشفاء بتعریف حقوق المصطفی " کا ایک مطالعہConcept of Protection of Honor of the Prophet: A Study of al- Al-Shifāʻ bi Taʻrīf Huqūq al-Mustafā by Qādī ʻIyād (Al-Qamar, 2023)
This paper studies the concept of Protection of honor  of the Prophet peace be upon him in the light of invaluable book “ al- Al-Shifāʻ bi Taʻrīf Huqūq al-Mustafā penned by the renowned scholar Qādī ʻIyād. From the principle stated by Qazi Ayaz, the article finds that when blood of a person is declared permissible in a blasphemy case, all the requirements of research and investigation should be fulfilled before the death penalty. It is very important to have reliable, clear and strong testimony to confirm the insolence and blasphemy of the Messenger of Allah. The accused will be released in case of insufficient evidence. The power of punishment rests only with the system and the ruler, and the ruler will punish when the evidence of the crime is provided.
Keywords: Honor; Prophet; Shifāʻ; Qādī; ʻIyād